Polyclonal antibody preparation against candidate tumour suppressor protein MIP for detection of its expression and localization in hepatocellular carcinoma - Minhua Wu; Shengchun Wang; Li Hu; Yanqing Liang; Yu Zhong; Minqin Jiang; Xiaoxia Ye (Biotechnology & Biotechnological Equipment, 2017)
MIP is a candidate tumour suppressor protein found in hepatocellular carcinoma. It can interact with different proteins in different subcellular locations. However, antibodies against MIP for testing purposes are still not available and this has hindered the research on MIP protein. In this study, the full coding sequence of MIP protein was cloned into the prokaryotic expression vector pET-28a. The recombinant protein his-MIP was expressed by IPTG (isopropyl β-D-1-thiogalactopyranoside) induction and purified by nickel-affinity chromatography, then used to immunize New Zealand rabbits to obtain a polyclonal antibody against MIP. The sensitivity and specificity of the antibody were evaluated by enzyme-linked immunosorbent assay and western blot. We used the obtained antibody to detect endogenous MIP protein in hepatocellular carcinoma (HCC) cells and normal human hepatic cells L-O2 and found decreased MIP expression in HCC cells. The immunohistochemistry results further showed that the expression level of MIP protein in HCC tissues was lower than that in the corresponding adjacent non-cancerous tissues. The MIP protein was distributed mainly in the cytoplasm in HCC. In adjacent tissues, however, high expression of MIP was detected in the nucleus in addition to the cytoplasm. The prepared polyclonal antibody against MIP provides a useful tool for further research on the functions of MIP.